Capital markets and institutions - Dougall, Herbert E. (Prentice-Hall, 1975)
The book makes extensive use of periodic institutinal balance sheet figure and annual floww-of-funds dât. Careful analysis of such information is necessary if sweeping generalizations are to be various markets.